Population, labour and migration in 19th- and 20th-century Germany - Bade, Klaus J. 1944- Hrsg (German historical perspectives series, 1987)
Klaus J. Bade (Herausgeber): Population, Labour and Migration in 19th and 20th Century Germany. (German History Perspectives, I.), Berg Publishers Limited, Leamington Spa, Hamburg, New York 1987. XII, 200 Seiten, 51 Mark